Предмет: Математика, автор: аминочк

 

1)a-(b+c+d-c-f); 2)a+(b+c+d-c-f); 3)a-(-b-c-d+c+f); 4) a+(-b-c-d-c-f) ; 5)a-(b-c+d-c+f) ; 6)a-(-b+c-d+c+F); 7)a+(b-c_d-c+f) ; 8)a+(b=c-d+c+f)

Ответы

Автор ответа: vadik209
0
1)a-(b+c+d-c-f)=a-b-c-d+c+f=a-b-d+f
2)
a+(b+c+d-c-f)=a+b+c+d-c-f=a+b+d-f
3)a-(-b-c-d+c+f)=a+b+c+d-c-f=a+b+d-f
4)a+(-b-c-d-c-f)=a-b-c-d-c-f=a-b-2c-d-f
5)a-(b-c+d-c+f)=a-b+c-d+c-f=a-b+2c-d-f
6)a-(-b+c-d+c+F)=a+b-c+d-c-f=a+b-2c+d-f
7)a+(b-c-d-c+f)=a+b-c-d-c+f=a+b-2c-d+f
8)a+(b+c-d+c+f)=a+b+c-d+c+f=a+b+2c-d+f

Похожие вопросы
Предмет: Математика, автор: ahmedov210677